2023
DOI: 10.1002/fft2.214
|View full text |Cite
|
Sign up to set email alerts
|

From salt pan to saucepan: Salicornia, a halophytic vegetable with an array of potential health benefits

Abstract: Domestication of novel crops from the wild is a key process that ensures food security by addressing adaptability to changing environments. These wild plants offer broader and unique health benefits beyond basic nutrition. Salinization resulted in a drastic reduction of arable land and freshwater intended for cultivation. Thus, the global food production is currently under a risk of meeting the demands. Salt‐tolerant plants (i.e., halophytes) are potential food candidates that can be used to increase the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 247 publications
0
2
0
Order By: Relevance
“…The importance of S. ramosissima as a commercial vegetable is increasing due to its organoleptic properties, including crunchy texture, slightly salty taste, and nutritional and functional properties. It is considered a reliable substitute for salt (NaCl) and, therefore, a promising functional ingredient to prevent cardiovascular diseases with appropriate levels of protein, dietary fibre, and minerals [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of S. ramosissima as a commercial vegetable is increasing due to its organoleptic properties, including crunchy texture, slightly salty taste, and nutritional and functional properties. It is considered a reliable substitute for salt (NaCl) and, therefore, a promising functional ingredient to prevent cardiovascular diseases with appropriate levels of protein, dietary fibre, and minerals [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinization, or the rise in saline content throughout the environment, poses a major liability to industrial agriculture in many regions of the world, leading to the degradation of arable lands at an alarming rate (Ekanayake et al, 2023). Saline deposition caused by saltwater intrusion in coastline groundwater sources may worsen due to climate change, leading to limited soil fertility and agricultural output (Calone et al, 2022).…”
Section: Role Of Salicornia As a Salt-tolerant Crop Against Salinizationmentioning
confidence: 99%
“…Cárdenas-Pérez et al (2021) have identified 64 species of Salicornia, with the most common being S. brachiata, S. arabica, S. europaea, S. fruticosa L., S. ramosissima, S. herbacea, and S. bigelvolii. The word "Salicornia" is inspired by the Latin words "sal" meaning "salt" and "cornu" meaning "a horn" due to being a saline vegetation with spiked tendrils (Ekanayake et al, 2023). Singh et al (2014) state that Salicornia typically develops to a length of 25 to 35 cm and has moist, flexible scaly foliage and horn-like terminal plantlets.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, functional foods are dietary components that offer health benefits beyond their basic nutrition. The growing interest in functional foods has driven a new market strategy for halophyte plants which exhibit distinct and conserved metabolic responses compared to conventional plants [4]. These responses are justified by their antioxidant and antimicrobial activities, making them ideal sources of bioactive molecules [5].…”
Section: Introductionmentioning
confidence: 99%